Concurrent juvenile myelomonocytic leukemia with thalassemia in a case with plasmodium knowlesi infection from Sabah, Malaysian Borneo - Mimi Azreen Abdullah; Saleh Mohammed Abdullah Saleh Mohammed; Subbiah Vijay Kumar; Mohammad Zahirul Hoque (MDPI, 2019)
A 3-year-old male child was presented with worsening abdominal pain, abdominal distension, lethargy, pallor and hepatosplenomegaly. The patient had multiple outpatient visits in the past and was treated with oral antibiotics, oral anthelmintic agents, albeit with minimal benefit. The patient also had non-neutropenic pyrexia spikes and oral ulcers. The patient was an adopted child; hence details about his biological parents’ previous history were unclear. Differential diagnosis of Chronic Myelomonocytic Leukemia (CMML), Juvenile Myelomonocytic Leukemia (JMML), Gaucher’s disease, Thalassemia and discrete pancreatic pathology was considered. Hemoglobin electrophoresis was indicative of thalassemia. Also, molecular detection method by polymerase chain reaction confirms a concurrent infection with Plasmodium knowlesi malaria. The BCR-ABL fusion gene was found to be negative. Correlating with peripheral monocytosis, bone marrow aspiration and trephine biopsy with blasts only 3-4% and hepatosplenomegaly, a diagnosis of JMML was established. We present a rare phenomenon with an overlap of signs and symptoms between JMML, underlying thalassemia, and Plasmodium knowlesi, posing a diagnostic challenge to physicians.